DETERMINATION OF THE AMOUNT OF PAULOWNIA FLOWERS AND VITAMINS IN THEIR COMPOSITION (Scientific journal of the Fergana State University, 2024)
In this research work, the vitamins contained in the leaves of the Paulownia plant introduced into our republic, growing in the territory of the Ferghana region, were studied by the Uscc method. According to the analysis of the result of the studied plant samples, it was found that they contain the following vitamins B-2, B-6, B-9 PP and C.